The Correlation of Prediabetes and Type 2 Diabetes With Adiposity in Adults - Sun, Juan; Liu, Zhen; Zhang, Zimu; Zeng, Ziyang; Kang, Weiming (Frontiers in Nutrition, 2022)
BACKGROUND: Fat metabolism is associated with type 2 diabetes mellitus (T2DM). This study aimed to evaluate the detailed relationship of T2DM and total percent fat (TPF) among adults. METHODS: Briefly, 28628 adults aged ≥18 years from both sexes in the National Health and Examination Survey (NHANES) 1999-2018 were involved in this study. Multivariable linear regression models were used to examine associations between T2DM status, disease duration of T2DM, serum glucose, glycohemoglobin (HbA1c) and TPF. RESULTS: After adjusting for sociodemographic covariates, health behaviors, hypertension, hypercholesterolemia, there was a positive association between T2DM status and TPF (β=1.84, 95% CI: 1.53~2.16) and a negative association between disease duration of T2DM and TPF (β=-0.04, 95% CI: -0.07~-0.00). Besides, when stratifying by T2DM status, we found positive association in serum glucose and HbA1c with TPF in participants without DM (serum glucose: β=1.42, 95% CI: 1.29~1.55; HbA1c: β=2.77, 95% CI: 2.51~3.03) but negative association in those with T2DM (serum glucose: -0.10, 95% CI: -0.15~-0.05; HbA1c: β=-0.13, 95% CI: -0.25~-0.01). CONCLUSIONS: This study indicated that adults with T2DM had significantly higher TPF compared with those without DM and TPF decreased as the disease duration of T2DM increase. And the relationships between serum glucose, HbA1c and TPF in participants with or without T2DM were opposite.